2006
DOI: 10.1182/blood-2005-07-2994
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ATP-induced release of matrix metalloproteinase 9 is mediated by the P2X7 receptor

Abstract: Matrix metalloproteinase-9 (MMP-9) activity is required for inflammatory response, leukocyte recruitment, and tumor invasion. There is increasing evidence suggesting that the P2X 7 receptor of mononuclear cells, which is activated by extracellular adenosine triphosphate (ATP), is involved in inflammatory responses. In this study, ATP caused a rapid release of MMP-9 and a moderate decrease in tissue inhibitor of metalloproteinase 1 (TIMP-1) release from human peripheral-blood mononuclear cells (PBMCs) over a 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 54 publications
5
117
3
Order By: Relevance
“…The role of other mast cell-derived cytokines (TNFα, IL-1β, IL-18, IL-25, and IL-33) in asthma pathogenesis was recently reviewed in detail [88,89]. It was also reported that ATP induces the release of matrix metalloproteinase-9 via a P2X 7 -dependent mechanism [95]. Mast cells are a rich source of this enzyme that participates in extracellular matrix remodeling by catalyzing the degradation of type IV collagen, the main component of the basement membrane [96].…”
Section: Purinergic Signaling In Allergic Airway Inflammation: Focus mentioning
confidence: 99%
“…The role of other mast cell-derived cytokines (TNFα, IL-1β, IL-18, IL-25, and IL-33) in asthma pathogenesis was recently reviewed in detail [88,89]. It was also reported that ATP induces the release of matrix metalloproteinase-9 via a P2X 7 -dependent mechanism [95]. Mast cells are a rich source of this enzyme that participates in extracellular matrix remodeling by catalyzing the degradation of type IV collagen, the main component of the basement membrane [96].…”
Section: Purinergic Signaling In Allergic Airway Inflammation: Focus mentioning
confidence: 99%
“…Besides the caspase-1 dependent processes described above, P2X7 receptor activation has also been shown to signal caspase-1 and IL-1β/IL-18 independent release of cathepsins [111,112], prostaglandin (PG)E 2 [8], phosphatidylserine [113], and matrix metalloproteinase 9 [114], all of which are implicated in cellular processes that play a defined role in inflammation.…”
Section: Macrophagesmentioning
confidence: 99%
“…Prolonged stimulation with ATP also leads to caspase-1 dependent, but IL-1β and IL-18 cytokine processing independent cell death in macrophages [87,98,99]. b P2X7 receptor activation has also been shown to signal caspase-1 and IL-1β/IL-18 independent release of cathepsins [111,112], PGE 2 [8], phosphatidylserine [113], and MMP-9 [114], all of which are implicated in cellular processes that play a defined role in inflammation. ATP is also reported to act as a long-range "find me" signal (chemoattractant) to recruit monocytes and macrophages [115].…”
Section: Macrophagesmentioning
confidence: 99%
“…Cellular K ϩ depletion is thought to be a costimulus for formation of the inflammasome 16,17 and secretion of proinflammatory cytokines interleukin-1␤ (IL-1␤) and IL-18. 18,19 Other downstream effects of P2X 7 activation include blebbing of the plasma membrane, 20 shedding of surface L-selectin and CD23, 21 rapid secretion of matrix metalloproteinase-9, 22 and activation of the caspase cascade leading to a form of apoptotic cell death. 23,24 The role of P2X 7 as a proinflammatory receptor is supported by results from the P2X 7 gene-deleted mouse, which shows major reduction in inflammatory responses to various noxious stimuli.…”
Section: Introductionmentioning
confidence: 99%